Martial Arts and Doping (the case of Sambo) - Bogdan Mytskan; Tetiana Mytskan; Yuryj Oliinyk; Georgiy Korobeynikov; Wojciech Cynarski; Stanisław Zaborniak; Carlos Gutiérrez-García (OVS LLC, 2022)
Background. Today, the problem of doping is the most well-known negative phenomenon in modern sport, which has become widespread in response to its active commercialization. The majority of people would agree that doping issue has moral and ethical basis, therefore the educational component of anti-doping policies is most promising in achieving the desired result - doping-free sport.  Research purpose. The study was aimed to investigate the peculiarities of the ideas sambo athletes may have about the problem of doping in modern sport. Materials and methods. The study involved 97 highly professional sambo athletes from 21 countries, namely Russia, Ukraine, Mexico, Japan, the USA, Canada, Cuba, Guatemala, Republic of Korea, Colombia, Paraguay, Venezuela, Peru, Brazil, Nicaragua, El Salvador, Dominican Republic, Puerto Rico, Honduras, Uruguay, and Costa Rica. Results. A survey conducted among the professional sambo athletes, participants of the 2018 World Cup, made it possible to establish their knowledge about and their attitude to doping. It became known that 76.29% of the athletes were well familiar with the doping control procedure, while 23.71% were not. At the same time, 78.35% of the respondents believed that they knew their rights and responsibilities during the doping control procedure, and 21.65% of the athletes did not. 77.32% of the respondents knew the organizer of doping control and 22.68% did not. Conclusions. The analysis of the study results and WADA statistics give grounds to state that the problem of doping in modern athletes remains an urgent problem in professional sports, including sambo.